Application Of Thought Stopping and Psycoeducation Therapy Families Towards Objective Loads And Resilience Family Caregiver In Caring For Clients Hypertension With Anxiety - Suseno, Akbar; Nurlinawati, Nurlinawati (Indonesian Journal of Community Development, 2024)
Background: Anxiety is a mental problem that is often experienced by people in everyday life, especially those who experience physical illnesses such as hypertension. Objective: Writing this report is intended to provide nursing interventions for nurses, family psychoeducation and thought stopping (TS) therapy so that clients can control anxiety, and the family's ability to care for anxious clients. Methods: Nursing actions for 1 hypertensive client with anxiety were reported in the form of a case series carried out in four meetings (five sessions). Results:  There were a decrease in signs of anxiety symptoms experienced due to trauma from an event. There is an increase in the client's ability to control anxiety and the family's ability to care for the client. Conclusion: This study is evidence based on the effectiveness of nursing actions by nurses and specialist nurses for clients with anxiety who require further evaluation with a larger sample size and more frequent meetings. In addition, it is necessary to research anxiety clients with physical illnesses by applying a combination of other therapies, such as cognitive behavioral therapy (CBT).